PELEPASAN NITROGEN DARI PANGKASAN POHON LEGUM PADA SISTEM BUDIDAYA PAGAR - Y. Nuraini; E. Handayanto (BUANA SAINS, 2006)
Decomposition and nitrogen mineralization of prunings from five species of legume hedgerow trees (Calliandra calothyrsus, Peltophorum dasyrrachis, Leucaena leucocephala, Gliricidia sepium, and Flemingia congesta) in relation to the pruning quality and methods of pruning application were studied in a laboratory and in the field. N mineralization of the prunings was tested upon application to the soil in a laboratory under controlled leaching and non-leeching conditions over the period of 14 weeks. The absolute decomposition rates of the prunings was measured using litterbags placed randomly on the soil surface or incorporated in the soil in the field over the period of 8 weeks. The results showed that the contribution of decomposing pruning materials to the soil was not only associated with their quality and with the leaching conditions, but also with the method of application of the prunings in the field. The decomposition and N release rate constants of the prunings declined in the order of Gliricidia> Leucaena > Flemingia > Calliandra > Peltophorum for all experiments carried out. The effect of quality of N release from legume prunings was modified by leaching conditions. Where there was no leaching, the protein-binding capacity of polyphenols in the prunings can play an important role in controlling the rate of N release. Under leaching conditions, the combined (lignin + polyphenol)/N ratio became an important quality factor in affecting the N release. The amounts of N released from the prunings placed on the soil surface were much smaller than those released from the incorporated prunings